Role of the Microbiome in the Pathogenesis of COVID-19 - De, Rituparna; Dutta, Shanta (Frontiers in Cellular and Infection Microbiology, 2022)
The ongoing pandemic COVID-19 is caused by the highly contagious single-stranded RNA virus, SARS-coronavirus 2 (SARS-CoV-2) which has a high rate of evolution like other RNA viruses. The first genome sequences of SARS-CoV-2 were available in early 2020. Subsequent whole-genome sequencing revealed that the virus had accumulated several mutations in genes associated with viral replication and pathogenesis. These variants showed enhanced transmissibility and infectivity. Soon after the first outbreak due to the wild type strain in December 2019, a genetic variant D614G emerged in late January-early February 2020 and became the dominant genotype worldwide. Thereafter, several variants emerged which were found to harbor mutations in essential viral genes encoding proteins which could act as drug and vaccine targets. Numerous vaccines have been successfully developed to assuage the burden of COVID-19. These have different rates of efficacy, including, although rarely, recently, a number of vaccinated individuals exhibited side-effects like thrombosis. However, the recent emergence of the Britain strain with 70% more transnmissibility and South African variants with higher resistance to vaccines at a time when several countries have approved these for mass immunization has raised tremendous concern regarding the long-lasting impact of currently available prophylaxis. Apart from studies addressing the pathophysiology, pathogenesis and therapeutic targets of SARS-CoV-2, analysis of the gut, oral, nasopharyngeal and lung microbiome dysbiosis has also been undertaken to find a link between the microbiome and pathogenesis of COVID-19. Therefore, in the current scenario of skepticism regarding vaccine efficacy and challenges over the direct effects of currently available drugs looming large investigation of alternative therapeutic avenues based on the microbiome can be a rewarding finding. This review presents the currently available understanding of microbiome dysbiosis and its association with cause and consequence of COVID-19. Taking cues from other inflammatory diseases we propose a hypothesis how the microbiome may be influencing homeostasis, pro-inflammatory condition and the onset of inflammation. This accentuates the importance of a healthy microbiome as a protective element to prevent the onset of COVID-19. Finally, the review attempts to identify areas where the application of microbiome research can help in reducing the burden of the disease.